(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
Regional Technical Implementation Unit Center for Natural Seed and Silk North Sulawesi Provincial Forestry Service is one of the bureaucratic organizations that has in the Development and Development of Natural silk in order to improve people’s welfare. The technical bureaucratic organization have not achieved optimal performance in carrying out tasks in the absence of silk thread produced in accordance with planning. This study aims to analyze why the organization Regional Technical Implementation Unit Center for Natural Seed and Silk North Sulawesi Provincial Forestry Service in carrying out the tasks of the development and development of natural silk in the context of improving the welfare of the community, no results have been obtained in accordance with the plan. This study uses qualitative methods with descriptive analysis Descriptive done in Regional Technical Implementation Unit Center for Natural Seed and Silk North Sulawesi Provincial Forestry Service The data used in this study are primary and secondary data. Data collection in this study was carried out with three main activities, namely interviews, observation and documentation. The results of this study indicate that the productivity indicators, the performance of Regional Technical Implementation Unit Center for Natural Seed and Silk North Sulawesi Provincial Forestry Service has been implemented efficiently but has not been fully effective, because there are results obtained but not in accordance with the expected planning that is producing high-quality and high-selling silk thread. This happens because it has not been supported with adequate human resources, budget and infrastructure in the process of carrying out the silkworm cultivation. Keywords: Organizational Performance, Natural silk